Examining the Effect of Body Shaming on Adolescent Mental Health - Siti Luthfiah; Yuda Syahputra (Asosiasi Asesmen Pendidikan (AAP), 2026)
This research was conducted at Jayakarta Junior High School. In the case of Jayakarta Junior High School, mental health issues arise due to lifestyle trends that are prevalent among adolescents, leading to bullying behavior towards those who do not conform to these trends. This bullying is known as body shaming. It is possible that this bullying can lead to damage to students' mental health. The purpose of this study is to analyze the relationship between body shaming and mental health. The research method used is regression analysis with a sample of 120 students selected based on certain criteria. The results show that Body shaming has an impact on the mental health of students. The results (Asymp. Sig. (2-tailed) show that Body shaming (> 0.495; sig = 0.000) and Mental health (> 0.852; sig = 0.000). This research also found that students of SMP Jayakarta who experienced body shaming had lower mental health scores compared to students who did not experience body shaming. The results of this study indicate that body shaming can be a risk factor for the mental health of students.